Особенности проектирования телефонной сети общего пользования на различных этапах развертывания NGN - Кадурин, С. А. (ХНУРЭ, 2009)
In this article the basic stages of development of POTS and ways of convergence of network of POTS and packet switching networks will be considered on the early stages NGN. On the basis of the conducted analysis of scenarios of construction of NGN and methods of providing of transmission of El streams between existent switch the mathematical model of task of synthesis of the imposed network of transmission of streams of attendant was built dialups.
Keywords: телефонная сеть общего пользования; развертывание NGN